Criticism of the curriculum and the Persian ratio of the idea of ​​illumination at Henry Corbin in the Arabic reading of his oriental studies (Damascus University Journal of arts and humanities sciences, 2025)
This study came revealing the Corbin philosophical approach, especially his works directed at Islamic and Persian philosophy from it, as it revealed his way of dealing with it, and his ability to understand the Arab and Iranian heritage. Despite the emergence of many editions, studies and translations on Islamic thought and Islamic philosophy, the presentation presented by Corbin in many of his writings, other than many previous ideas on Islamic thought that affected Western philosophy since the time of the Middle Ages, for his personal connection with Islamic thinkers. On the pages of this study,Corbin's endeavor to revive the Persian source and emphasize his role in the theory of Sahrurdish brightness, and from here his bias was to study Iranian philosophers and research in matters of gratitude and spiritual spiritual Islam, especially Sahrurdi. Hence the criticism directed at his ideas about the concept of (illumination)by a number of Arab researchers, whose methodology took each with a different point of view from the other.
Keywords: The curriculum; Illumination; Suhrawardy; Persian origin; Criticism.